2013
DOI: 10.1186/1477-7525-11-204
|View full text |Cite
|
Sign up to set email alerts
|

Health-related quality of life in children and adolescents with celiac disease: survey of a population from central Italy

Abstract: BackgroundCeliac Disease (CD) is an increasingly common autoimmune disorder. It requires a strict lifelong adherence to a gluten-free diet (GFD) which can influence health-related quality of life (HRQOL). This study assesses HRQOL in children and adolescents with CD and explores how several demographic and clinical characteristics and GFD adherence affect their perceived health status.MethodsWe recruited 140 consecutive children and adolescents with CD confirmed by small bowel biopsy. HRQOL was assessed using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
72
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(79 citation statements)
references
References 32 publications
4
72
1
1
Order By: Relevance
“…Altobeli et al . compared generic HRQoL scores of 64 Italian teenagers with CD (14–18 years; mean age 14.2 years) to normative data from 3221 adolescents (14–17 years) using the validated SF‐12 tool. Although teenagers with CD scored lower for mental health scores compared to the control population ( P < 0.001), neither compliance, nor perceived difficulty of compliance was associated with this score.…”
Section: Adherence To the Gluten‐free Diet And Health‐related Qualitymentioning
confidence: 99%
“…Altobeli et al . compared generic HRQoL scores of 64 Italian teenagers with CD (14–18 years; mean age 14.2 years) to normative data from 3221 adolescents (14–17 years) using the validated SF‐12 tool. Although teenagers with CD scored lower for mental health scores compared to the control population ( P < 0.001), neither compliance, nor perceived difficulty of compliance was associated with this score.…”
Section: Adherence To the Gluten‐free Diet And Health‐related Qualitymentioning
confidence: 99%
“…In children, as well as in adults, a chronic illness, like CD, may interfere with daily life and impact QOL. So using different instruments [9][10][11][12]. By using a qualitative method of research, the Critical Incident Technique, we recently reported on the impact of the GFD on daily life of children with treated CD.…”
Section: Introductionmentioning
confidence: 98%
“…The stigma of a chronic disorder and the need for major dietary restrictions increase the self‐perceived burden of illness and may adversely affect patient's QOL. In patients with celiac disease (CD), poor adherence to gluten‐free diet (GFD), social and economic issues associated with lifelong GFD, associated medical comorbidities, and several intestinal as well as extraintestinal symptoms in CD are also associated with a poor HR‐QOL . Both generic (general) and individual (specific) tools can be used to measure the HR‐QOL in CD .…”
Section: Introductionmentioning
confidence: 99%